A rare presentation of non-cirrhotic portal fibrosis in pregnancy: a case report - Mishra, Mona; Sachdeva, Poonam; Mala, Y. M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Non cirrhotic portal fibrosis (NCPF) in pregnancy is a rare occurrence with an in hospital incidence of 0.009%. Management in pregnancy is challenging due to lack of standard protocol and paucity of extensive research in current literature. NCPF if untreated can lead to catastrophic complications and lead to significant maternal morbidity and mortality. We present a case report of a 23-year-old G2A1 female presenting for the first time in pregnancy at 34 weeks’ gestation as a case of NCPF with prelabour rupture of membranes. She was managed with multidisciplinary approach and underwent normal vaginal delivery with satisfactory feto-maternal outcome. NCPF in pregnancy is uncommon and a thorough knowledge about the condition and systematic management at a tertiary care center with a multidisciplinary team is essential. Its prognosis in pregnancy is usually good if managed promptly and systematically.